Gênero, loucura e mídia : textualidades em torno do “Free Britney” - Valquiria Lopes Rabelo (2023)
In this dissertation, we take the media textualities surrounding the “Free Britney” movement as a privileged field to observe discursive intertwinements between gender and madness. To problematize the phenomenon, we propose articulating Erving Goffman’s notion of stigma with Kimberlé Crenshaw's concept of intersectionality. Subsequently, we undertake a historical investigation guided by the insights of Elaine Showalter, Eleni Varikas, and Maria Rita Kehl, who assist us in unraveling the connections that link “Woman” and “Madness” in the Western imagination. Building on this theoretical-methodological framework, we analyze the generative trajectory of meaning emerging from the empiricism, according to the model organized by Greimasian Tensive Semiotics. Following the indications of Gonzalo Abril, we also discuss the sensitive and pragmatic relations produced by the components of the synoptic space. Ultimately, we acknowledge four recurring aspects in the portrayal of the pop diva Britney Spears: a) her depiction through a gaze identified with the male observer's desire for authority and sexual domination; b) the monitoring and pathologizing of her deviations from the heteronormative referential of gender performance and sexuality; c) the contradictions between a supposed fragility, traditionally attributed to women, and the perception of peril cast by the stereotype around psychiatric patients; and d) an implicit discredit of her statements and claims. We conclude the study with a discussion on the performative role of media in reinforcing norms and stigmatizing texts.